PENINGKATAN KOMPETENSI GURU IPA DI KABUPATEN GARUT MELALUI PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN FISIKA BERBASIS AUGMENTED REALITY - Ali Ismail; Surya Gumilar; Irma Fitria Amalia; Purnomo Sidiq (Lembaga Pengabdian kepada Masyarakat Institut Pendidikan Indonesia Garut, 2018)
This community service activity aims to provide skills for Natural Sciences teachers in Garut district to create augmented reality based learning media. Through the use of good and appropriate media, the delivery of material can be better absorbed by students. So that later students are expected to be easier to understand the concepts. The service activities consist of two stages, the first stage is socialization and the second stage is training. The socialization and training were attended by science MGMP teachers in Garut district. The training material is the use of augmented reality as an alternative learning media in science learning. The results showed that community service went well and smoothly. Based on the overall questionnaire results the teachers responded positively related to the implementation of this training. The teacher seemed very enthusiastic in listening to the explanation and practicing what the speaker said. In addition, the teachers stated that through the training, they obtained many benefits related to the addition of knowledge about alternative learning media that could be applied in science learning, even they felt an increase in creativity in making learning media. The obstacles that arise at this training stage are the problems of time that are felt lacking for training, therefore they suggest that ongoing training be held related to the making of learning media using augmented reality or other media.